The neurobiology of pain: (molecular and cellular neurobiology) - Hunt, Stephen P.; Koltzenburg, Martin (Molecular and cellular neurobiology series, 2005)
Within the last decade we have seen major new advances in the neurobiology of pain. The topic has emerged as a separate field of study in its own right. This volume presents a state-of-the-art account of the neurobiological basis of pain by leading scientists in this field